ROS-induced dramatic lipid changes in Arabidopsis - Tianlin Jin (Taylor & Francis Group, 2021)
Objectives: The beneficial role of ROS was probably in promoting intercellular communication by modifying membrane constituents [Liang D. A salutary role of reactive oxygen species in intercellular tunnel-mediated communication. Front Cell Dev Biol. 2018;6:2]. We investigated how the membrane lipids were responding to ROS and ROS inhibitors. Methods: To examine how ROS affected the lipid profiles, we used thin-layer chromatography to characterize lipid profiles in Arabidopsis plants. Then, the confocal microscopy imaging was used to confirm the change of membrane lipid in a plasma membrane marker line exposed to ROS and ROS inhibitors. Results: We found the relative contents of most lipids in H2O2-treated Arabidopsis plants were increased in roots, rather than in shoots. The increased fluorescent signal of membrane marker induced by H2O2 was mainly enriched in the conductive parts of roots. Several ROS inhibitors also strongly affected the lipid profiles. Among them, diethyldithiocarbamate (DDC) can progressively change the lipid profiles with treatment going on. Membrane marker signal was mainly accumulated in the root tips and epidermal cells after treatment by DDC. Discussion: H2O2 may enhance intercellular communication by inducing different lipid species in the conductive parts of roots. The lipid profiles were widely responding to various ROS reagents and might play a role in intercellular signaling.